An amidoxime-functionalized polypropylene fiber: Competitive removal of Cu(II), Pb(II) and Zn(II) from wastewater and subsequent sequestration in cement mortar. (20th November 2020) - Zhao, Dezhi; Wang, Zheng; Lu, Shuang; Shi, Xianming
Abstract: Eco-friendly adsorbents for removing heavy metals from wastewater are urgently needed. This work fabricated an amidoxime-modified polypropylene (PP) fiber as a cost-effective and recyclable adsorbent to remove heavy metals. The laboratory study aimed to evaluate the competitive adsorption of Cu(II), Pb(II) and Zn(II) onto AO-PP fiber in aqueous solutions. The adsorption isothermal data fitted the Langmuir isotherm well, and the maximum adsorption capacities (mg/g) were in the order of Cu (47.23)>Pb (45.64)>Zn (37.78) when applying the Langmuir isotherm at pH 5.0. Adsorption equilibrium could be reached within 90 min. The adsorption was pH-dependent and followed the pseudo-second-order model well. The adsorption can be explained by the coordination between N- and O-containing groups and the metallic ions. Metallic ion affinity, steric hindrance, and covalent index were the main factors affecting the competitive adsorption behavior. Regeneration experiments revealed that the obtained adsorbent maintained favorable adsorption capacity even after 20 cycles. Cement mortars incorporating the metal-adsorbed fiber exhibited improved mechanical properties and satisfactory leaching performance. This work experimentally validated the effective use of AO-PP fiber to capture heavy metals from wastewater as well as subsequent sequestration of the recycled fibers in a suitable material matrix, providing a new reference for heavy metal harvesting and final disposal. Graphical abstract: Image 1 Highlights: Functionalized polypropylene fiber to remove Pb, Cu and Zn ions from wastewater. The adsorptions followed pseudo-second order kinetic model and Langmuir model. The adsorbent showed favorable adsorption capacity and good reusability. The metal-adsorbed adsorbent was further upcycled in cement mortars. The mortar showed improved mechanical properties and good leaching performance.